Shear characteristics of Lean Duplex Stainless Steel (LDSS) rectangular hollow beams. (May 2017) - Sonu, J.K; Singh, Konjengbam Darunkumar
Abstract: A numerical investigation on the shear characteristics of Lean Duplex Stainless Steel (LDSS) rectangular hollow beams are presented in this paper, through a parametric study, using the commercial finite element software, Abaqus. Effects of key cross sectional parameters viz., flange thickness ( t f ), flange width ( w f ), web thickness ( t w ) and shear span ( a ) have been considered, keeping the height of the web ( h w ) constant. It is observed that increasing flange thickness for the same web thickness, can enhance both shear capacity and ductility. The shear capacity of the beam is seen to decrease with increasing shear span, the decrease being 32–36%, for 100% increase in shear span ( a / h w ). The effect of increasing flange width is found to be relatively significant for stockier cross sections as compared to that of slender sections. Three failure mechanisms have been identified viz., 1) shear dominant, 2) bending dominant, and 3) combined shear and bending. In general, both EN 1993-1-4 (2006/A1:2015) and DSM are found to be applicable for the shear design of LDSS rectangular hollow beams. Possible modifications to both EN 1993-1-4 (2006/A1:2015) and DSM have been suggested by bifurcating into two span ratios: 1) a / h w ≤ 1.0 and 2) 1 < a / hw ≤ 2.0.